Health economics analysis of pegfilgrastim in the prophylaxis of febrile neutropenia (FN) in Italy. Issue 2 (12th March 2012) - Lebboroni, M.; Rosti, G.; Cerchiari, A.; Katz, P.
Abstract : Background: FN is a serious side-effect of myelotoxic chemotherapy. G-CSF prophylaxis decreases FN incidence and reduces related morbidity and mortality. Purpose: Evaluate the budgetary impact of primary (PP) and secondary prophylaxis (SP) of pegfilgrastim for the Italian NHS in two scenarios: first when increasing pegfilgrastim use in PP and SP from the 2011 patient share to the estimated 2013 share; and second when shifting all usage to only PP pegfilgrastim. Materials and methods: A decision-analytic model calculated the budget impact. Costs considered were: direct G-CSF healthcare costs, G-CSFs administration costs and costs of FN-related events. G-CSF costs were calculated by using the maximum selling price to hospitals. Filgrastim biosimilar lower costs and filgrastim branded cost were considered together by using a weighted average cost based on market shares. Prophylaxis strategies included in the first scenario were filgrastim, pegfilgrastim, lenograstim and antibiotics; estimated pegfilgrastim PP use increased from 12.8% (2011) to 15.7% (2013) and SP use increased from 8.5% (2011) to 10.5% (2013). Chemotherapy regimens included CHOP(R) for non-Hodgkin's lymphoma (NHL); and AC-T, TAC and TC for breast cancer. Annual incidence of NHL and breast cancer (stage II and III) was estimated by applying incidence rates from the German Krebregister to the Italian population. Results: A negative budget impact value represents a cost reduction. Regarding NHL (N=10, 800), the budget impact for the first scenario was €-261 K for CHOP and €-255 K for CHOP-R. The budget impact for the second scenario was €-2, 76 mio for CHOP and €-2, 55 mio for CHOP-R. For stage II breast cancer (N=14, 970) the budget impact for the first scenario was €-370 K for AC-T, €-236 K for TAC and €-234 K for TC, while the budget impact for the second scenario was €-1, 82 mio, €-396 K and €-2, 33 mio, respectively. Stage III breast cancer (N=1, 950) followed the same trend as stage II. Conclusions: In our budget impact model, a prophylaxis strategy including pegfilgrastim as PP or SP reduced costs for the Italian NHS in breast cancer and NHL.